Penerapan Model Pembelajaran Discovery Learning Menggunakan Bantuan Alat Hitung dalam Materi Hitung Dasar untuk Meningkatkan Hasil Belajar Siswa TK Kedungrejo Bojonegoro - Setyowati, Suci Yongki (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
Discovery learning is a learning model that has a lot of influence on students' learning abilities. Therefore, this research aims to improve the activities and learning outcomes of Kedungrejo Bojonegoro Kindergarten students in basic introduction to arithmetic material through the Discovery Learning learning model. This research was conducted at the Dharma Wanita Kindergarten in Kedungrejo village, Bojonegoro, East Java in the odd semester of the 2023/2024 academic year with 10 students as the subject. This type of research is classroom action research which consists of planning, implementing actions, observing and reflecting using the Discovery Learning learning model. Student learning activity data was collected using the observation method. Student learning activity data obtained was analyzed using descriptive statistics. Individual student activity data is analyzed based on the percentage of occurrence of each learning activity item carried out by students during the learning process. Meanwhile, to measure student learning outcome data, the scoring method is used by giving tests in the form of questions according to the subject matter that has been given. Tests are given at the end of each lesson. From the test results given, the use of the discovery learning model can increase the learning activities of Dharma Wanita Kindergarten students in Kedungrejo. In this study, researchers divided learning into 2 periods. Period 1 learning was carried out without using the discovery learning learning model. The results showed that only 30% of students were declared complete, then 70% of students were declared incomplete. Meanwhile, in period 2, 60% of students were declared to have completed their studies and 40% were declared incomplete. From these results, it can be seen that the use of the discovery learning model is able to improve student learning outcomes.